A világörökségek szerepe a nyugat-dunántúli régió turizmusfejlesztésében - Kulbert, Zsófia (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
When we advert the trends of the tourism of the past years, we can see that those pro-duces, which are based on unique experiences, became more popular, than other ones. In the other side, nowadays the experience is beginning to turn into a new category of tourism very forcefully. In the ground of West-Transdanubien region there are two spot, which are parts of the World-Heritage: The Arch abbey of Pannonhalma, which was getting into to the list in 1996, and the Fertő culture land. It may be hypothesized, that the World Heritage denomi-nation involves a rise in the number of visitors. The circumstances at the moment are not so rewarding, to fulfil the hopes, what the tourism appends to it; it would be need complex innovate, which includes some important component: to develop the policy of tourism and the efficient management.